Isbat Nikah Dalam Hukum Islam Dan Perundang-Undangan Di Indonesia - Meita Djohan Oelangan (Law Faculty of Universitas Bandar Lampung, 2013)
Undocumented marriage or tacit, or popular with the term âNikah Sirriâ, is a phenomenon that often occurs in the community.. The proof is, many requests of isbat (confirmation of marriage) or marriage legalization proposed at the Court of Religion by both husband and wife, that undocumented marriage took place before the adoption of the Marriage Law Number: 1 of 1974 nor after the adoption of its legislation.The research method used is juridical normative jurisdiction, the data used are secondary data. The data analysis was done by qualitative analysis.The results of research in this thesis turned out to be, not all requests of marriage confirmation of undocumented marriages can be granted. Religious Court will grant the confirmation of marriage that qualified one of criteria in Article 7, paragraph (3) letter a to letter e Compilation of Islamic Law and the marriage proven at trial appropriate according to Islamic Law, and theres no violation of marriage ban according to Islamic law and state law.